Mengingkatkan Kemampuan Guru Menulis Karya Ilmiah Dengan Menghadirkan Guru Tamu Di Sekolah - I Nyoman Tingkat (Jayapangus Press, 2020)
The aim of this article is to know the effectiveness of the presence of a guest teacher for the teachers in SMA Negeri 1 Kuta Selatan to produce a various research. Since PKG (Penilaian Kinerja Guru) has been implementing from January 1, 2013, teachers could not have a promotion in 2 years if they were not an administrator or in IV/a level. It happened because it needed a credit score of the continuing professional development in every preferment if teachers wanted to have a promotion from III/a to III/b. Then, for III/b and above, they need to complete the credit score through a scientific publication and or an innovative work. This research used literature review, questionnaire, observation sheets and interview in collecting the data. Meanwhile the data analysis used was descriptive qualitative. The results showed two points. First, the presence of a guest teacher through a workshop in SMA N 1 Kuta Selatan could increase teachers’ ability to produce a research and an innovative work. The impact was on the teacher’s promotion in the first cycle from no one to three people (7,69%) in the second cycle. The number of teachers who made proposal and were ready to present it in an academic conference were increasing from three people (7,69%) in the first cycle to eight people (20,51%) in the second cycle. Teachers who wrote scientific articles in an ISSN journal were also increasing from four people (10,25%) in the first cycle to five people (12,82%) in the second cycle. Second, the teachers’ response were also increasing toward the presence of a guest teacher from 72,22%, which was a neutral category in the first cycle, to 83,33%, a good category in the second cycle. Its effect the students’ achievements, from 72 medals in the first cycle to 88 medals in the second cycle.